EKRANISASI NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA KE FILM SURGA YANG TAK DIRINDUKAN SUTRADARA KUNTZ AGUS - Asmara, Mira; WS, Hasanuddin; Nst., Muhammad Ismail (Universitas Negeri Padang, 2017)
This study is aimed to: (a) describe the story episodes in the novel of Surga Yang Tak Dirindukan by Asma Nadia, (b) describe the episodes of the film Surga Yang Tak Dirindukan directed by Kuntz Agus, (c) describe the comparison of episodes between the story in the novel of Surga Yang Tak Dirindukan by Asma Nadia and the film of Surga Yang Tak Dirindukan directed by Kuntz Agus.This research is a qualitative study using descriptive methods. Data of this research is the story episodes in the novel of Surga Yang Tak Dirindukan by Asma Nadia and the film of Surga Yang Tak Dirindukan directed by Kuntz Agus. Technically, data was collected through three stages: the first stage is to read the novel of Surga Yang Tak Dirindukan by Asma Nadia that will be followed by watching the film of Surga Yang Tak Dirindukan directed by Kuntz Agus. The second stage is to inventoried, identify issues related to episodes in the novel of Surga Yang Tak Dirindukan by Asma Nadia and the film of Surga Yang Tak Dirindukan directed by Kuntz Agus. The third stage is the data classification step into the data format. The data validation techniques is created by using technique of detailed description. Analyzing technique is done by interpret every period of episodes which is based on ecranisation theory.Results which obtained from this research is found 209 episodes in the novel of Surga Yang Tak Dirindukan by Asma Nadia and found 185 story episodes in the film of Surga Yang Tak Dirindukan directed by Kuntz Agus. Story episodes that are equally exist in the novel of Surga Yang Tak Dirindukan by Asma Nadia and in the film of Surga Yang Tak Dirindukan directed by Kuntz Agus, there're few changing in variety of events, characters and background which found 92 episodes inside the story. It happened due to the creativity from the director when adapting a novel into a movie.Keywords : novel, movie, ekranisasi, episode